CATEGORY "MILITARY PROPERTY" AS AN OBJECT OF ADMINISTRATIVE AND LEGAL REGULATION - Kapinus, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article identifies categories and concepts as forms of human thinking and, in accordance with the laws of logic, analyzes how "property" and "military property" are related as legal categories. It is proved that the property, as a general rule, has the following qualifications: civil / economic nature, value determination and accounting in the form prescribed by law. With regard to military property, along with the above features, there are specific ones that indicate the administrative and legal nature of military property, especially given the relationship which is the subject of such property. These are: political conditionality; centralization of military property management; imperative regulation of military property; prevalence of coercive measures; special legal regime of military property. It is noted that the legislator in the concept of the legal regime of property includes the concept of property, the list of bodies that manage this property, the peculiarities of its status, the order of registration and write-off of military property, rules for its formation and alienation. Emphasis is placed on the fact that "legal category" – is a generic concept for a set of legal phenomena, facts, elements of content and forms which give each category characteristic legal features and separate it from other categories. It is concluded that such a legal category as military property is a generic cross-sectoral concept. It is determined that military property as a legal category is a state material good with certain economic, economic utility and inherent characteristics, which is temporarily or permanently transferred to military units, institutions and organizations to ensure the tasks of the Armed Forces of Ukraine.